FACTORS RELATED TO ECTOPIC PREGNANCY IN RSUD R.A KARTINI JEPARA - Muhammad Fikri Hanif Raza Pradana; Yuli Trisetiyono; Bambang Hariyana; Muhammad Besari Adi Pramono (Jurnal Kedokteran Diponegoro, 2021)
Background: Ectopic Pregnancy (EP) is a pregnancy outside the womb that ends with a rupture. Bleeding is one of the causes of the increase in Maternal Mortality Rate (MMR) by 24.5% in Central Java Province in 2017. Research to determine the factors associated with the occurrence of EP needs to be known so that the incidence of EP and MMR in Indonesia can be controlled.